Analysis of the Low Acceptance of Male Family Planning in RT 003 RW 01 Kebagusan Pasar Minggu, South Jakarta - Lilik Susilowati; Ella Nurlelawati; Laurentia Dewi (Akademi Keperawatan RSPAD Gatot Soebroto, 2022)
Family planning is an effort to help individuals or couples, among other things, to prevent unwanted births or vice versa for couples who want children, to regulate pregnancy intervals, to control the time of birth related to the age of the parents, to determine the number of children in the family. This study aims to analyze the low number of male family planning acceptors in RT 003 RW 01 Kebagusan Pasar Minggu, South Jakarta. The sampling technique was carried out by purposive sampling technique. With a total sample of 65 respondents. Data analysis was performed by Fisher's exact test. Shows that the value of p <0.05 means that there is a significant relationship between the dependent and independent variables, a value of p> 0.05 means that there is no significant relationship between the dependent and independent variables. Male family planning acceptors in Rt 002 Rw 01 Kebagusan Pasar Minggu, South Jakarta, totaled 13 respondents (20%). Of the 65 respondents, knowledge of male family planning acceptors who knew about male contraceptives (95%), male family planning acceptors who did not know about male contraceptives (5%), education of male family planning acceptors respondents (12%), Middle school (54%), vocational school (31%), university (3%), male family planning acceptors who receive support from their wives (44.6%), male family planning acceptors who are correct (72.3%), age of male family planning acceptor respondents 20-35 years (44.6%), 36-50 years (49.2%), male family planning acceptor respondents who received support from health personnel (43.1%), family planning acceptor respondents men who received socio-cultural support (44.6%). Factors associated with low male acceptors of Family planning are education, wife's participation, perception, age, health worker participation, and socio-culture. From each of these variables, there is a significant relationship between the dependent variable and the independent variable. The results of the research are expected to be a source of knowledge and information so that men of childbearing age who are already married participate in becoming male acceptors of Family planning